Impaired sodium‐evoked paraventricular nucleus neuronal activation and blood pressure regulation in conscious Sprague–Dawley rats lacking central Gαi2 proteins. (19th October 2015) - Carmichael, C. Y.; Carmichael, A. C. T.; Kuwabara, J. T.; Cunningham, J. T.; Wainford, R. D.
Abstract: Aim: We determined the role of brain G α i2 proteins in mediating the neural and humoral responses of conscious male Sprague–Dawley rats to acute peripheral sodium challenge. Methods: Rats pre‐treated (24‐h) intracerebroventricularly with a targeted oligodeoxynucleotide (ODN) (25  μ g per 5  μ L) to downregulate brain G α i2 protein expression or a scrambled (SCR) control ODN were challenged with an acute sodium load (intravenous bolus 3 m NaCl; 0.14 mL per 100 g), and cardiovascular parameters were monitored for 120 min. In additional groups, hypothalamic paraventricular nucleus (PVN) Fos immunoreactivity was examined at baseline, 40, and 100 min post‐sodium challenge. Results: In response to intravenous hypertonic saline (HS), no difference was observed in peak change in mean arterial pressure between groups. In SCR ODN pre‐treated rats, arterial pressure returned to baseline by 100 min, while it remained elevated in G α i2 ODN pre‐treated rats ( P  <   0.05). No difference between groups was observed in sodium‐evoked increases in Fos‐positive magnocellular neurons or vasopressin release. V1a receptor antagonism failed to block the prolonged elevation of arterial pressure in G α i2 ODN pre‐treated rats. A significantly greater number of Fos‐positive ventrolateral parvocellular, lateral parvocellular, and medial parvocellular neurons were observed in SCR vs. G α i2 ODN pre‐treated rats at 40 and 100 min post‐HS challenge ( P  <   0.05). In SCR, but not G α i2 ODN pre‐treated rats, HS evoked suppression of plasma norepinephrine ( P  <   0.05). Conclusion: This highlights G α i2 protein signal transduction as a novel central mechanism acting to differentially influence PVN parvocellular neuronal activation, sympathetic outflow, and arterial pressure in response to acute HS, independently of actions on magnocellular neurons and vasopressin release.